Critical evaluation of 2-ethylhexyl acrylate dermal carcinogenicity studies using contemporary criteria. (15th September 2018) - Murphy, Sandra; Ellis-Hutchings, Robert; Finch, Lavorgie; Welz, Stefanie; Wiench, Karin
Abstract: Skin tumors have been observed in C3H/HeJ mice following treatment with high and strongly irritating concentrations of 2-ethylhexyl acrylate (2-EHA). Dermal carcinogenicity studies performed with 2-EHA are reviewed, contrasting the results in two mouse strains (C3H/HeJ and NMRI) under different dosing regimens. Application of contemporary evaluation criteria to the existing dermal carcinogenicity dataset demonstrates that 2-EHA induces skin tumors only at concentrations exceeding an maximum tolerated dose (MTD) and in the immune-dysregulated C3H/HeJ mouse model. Overall, the available chronic toxicity and genotoxicity data on 2-EHA support a non-genotoxic chemical irritant mechanism, whereby chronic irritation leads to inflammation, tissue injury, and wound repair, the latter of which is disrupted in C3H/HeJ mice and leads to tumor formation. Tumor response information in excess of an MTD should not be considered in a human hazard or risk assessment paradigm. For the purposes of an appropriate hazard assessment, 2-EHA did not cause or initiate dermal carcinogenesis in an immune competent (NMRI) mouse model, and, even in the immune compromised C3H/HeJ model, did not induce skin tumors at doses which did not exceed the MTD.